Ways of Preventing Depravity in the Light of the Code of Canon Law 1983 - SAJ, MAREK (Prawo Kanoniczne, 2019)
The topic of depravity is present not only in moral theology, but it remains the subject of interest of the canon law. This phrase is present in numerous canons of the Code of Canon Law 1983 in the context of different legal situations. In this paper we turn attention to these situations which might result in depravity. Yet, depravity has not taken place, however the situation borders on it. Hence there are following situations analysed: these relations of clergy which may cause depravity, preventing depravity when Eucharist is celebrated in a non-Catholic temple; preventing depravity in case of confession with assistance of a translator, depravity vs. keeping secret of in case of marriage celebrated in secret, a danger of depravity in case of funeral of public sinners; keeping secret in the court trials, both criminal and contentious ones; prevention of depravity in hearing witnesses; preventive ordinations of the ordinary. In these situations the law maker advises to undertake proper actions to prevent depravity.